Australia in the 1990's - Bereson, Itiel, 1927-2016. (Port Melbourne, Vic. : Echidna Books, 2000)
Life in Australia has changed dramatically since the beginning of the 20th century. From horse-drawn vehicles to fast sleek cars, and from telegraph cables to the Internet, developments in technology have had an enormous impact on Australia over the past 100 years.
Includes index.
Bibliography: p. 31
White
For primary/secondary school students.
Keywords: Australia -- Politics and government -- 1990- -- Juvenile literature; Australia -- History -- 1990- -- Juvenile literature; Australia -- Social conditions -- 1990- -- Juvenile literature; Australia -- Social life and customs -- 1990- -- Juvenile literature